RI 2905 The Explosibility Of Suspensions Of Soap Dust In Air - David F. Smith (The National Institute for Occupational Safety and Health (NIOSH), 1928)
[The U. S. Bureau of Mines at its Pittsburgh Experiment Station is frequently called upon to determine by laboratory tests the explosibility of suspensions in air of various dusts encountered in mines and elsewhere. Not all dusts which are combustible or contain combustible material will form explosive mixtures with air under ordinary conditions of temperature and pressure. They may not be highly combustible enough. They may contain a considerable amount of inert or non-combustible material or, the dust particles may not, be fine enough to form explosive mixtures. A knowledge off the chemical composition of a dust together with a determination of the size of the particles often gives valuable indications. But in many cases actual explosibility tests are necessary. Such a case is evidently that of powdered soap, whose explosibility hazard the Bureau was recently called upon to determine, Although an explosion which occurred in a soap plant as early as 1890 was attributed4 to powdered soap, it is apparent, due to the great number of inquiries received by the Bureau, that the hazard presented by powdered soap has not been at all generally appreciated. To the writers' knowledge, no extensive investigation of the explosibility of powdered soaps has been made. It is only recently that pure powdered soap has been manufactured on a large scale. The familiar "soap powder" in the past was usually a mixture of soap with a relatively large quantity of sodium carbonate. Often it contained large amounts of moisture and abrasive material. Even a highly combustible dust when mixed with large quantities of inert dust will not form explosive mixtures with air. Pure powdered soap, however, presents a different aspect. Pure soap is formed by combination of alkali (incombustible material) with fatty acid (combustible material). Toilet soap fray also contain a certain amount of glycerin and essential oil winch, being combustible influence the explosibility]